Assessment of Seasonal Change in Ground Water Quality Index and Physio-Chemical Parameters for Babhulgaon Village Taluka-Yeola District-Nashik (Maharashtra) India - Sanap, Santosh Tukaram; Kasliwal, Saurabh Sanjay; Pote, Rohit Kailas; Gawande, Yogesh Bhagwanrao; Gaikwad, Akash Digambar; Sanap, Sajan Sitaram (Asian Journal of Biological and Life Sciences, 2025)
Background: The most basic human requirement is water. Both surface water and ground water are quickly being used as the world's population grows. Because groundwater and surface water are both utilized for drinking and other objectives, it is also vital to assess the quality of groundwater. Groundwater quality is significantly impacted by climate change, although seasonal variations also have an impact. Seasonal analysis of groundwater quality might also reveal discernible fluctuations. Materials and Methods: The primary objective of this investigation is to examine how the physio-chemical properties of groundwater and relative soil changes with the seasons. It also focuses on the drinking water quality index of Babhulgaon hamlet in the Nashik region. In the wet, winter, and summer seasons, soil and groundwater samples were gathered. Four samples of soil and water from bore wells in the Babhulgaon cultivation region were examined for general and physio-chemical characteristics. Results: Each season's four samples' groundwater was examined. The study area's Water Quality Index classified the water as "good water" during the winter and rainy seasons, but the summer sample had a higher WQI and was classified as "poor water." Conclusion: Analysis of soil samples from various seasons reveals variations in soil characteristics that affect soil quality. The winter soil sample's phosphorus content is higher than the ideal threshold.
Keywords: Babhulgaon Village; Groundwater; Physical-Chemical Parameters; Seasonal Impacts Soil Quality; Water Quality Index